Effects of small molecule inhibitors targeting PI3K, EGFR, IGF-1R, MTOR, SMAD3 and MEK in tube formation and 3-D spheroid assay - Ng, Chin Tat (2014)
Angiogenesis is the process where new blood capillaries are formed from the preexisting blood vessels. The MEK/ERK and PI3K/Akt signaling pathways are involved in the processes that drive cancer progression such as cell motility, metastasis and angiogenesis. The cellular events in angiogenesis which include endothelial cell migration, invasion and differentiation contribute significant role to cancer metastasis. Inhibition of angiogenesis via disruption of signaling pathways appears to be a rational therapeutic strategy. Hence, there is need to investigate the role of PI3K-AKT and MEKERK signaling in microvascular endothelial cells. In this study, we investigated the role of PI3K/AKT and MEK/ERK pathway in two microvascular endothelial cell lines, namely, HMEC-1 (SV40-immortalized) and TIME (telomerase-immortalized). The specific objectives of the study were (i) to investigate the effect of blocking PI3K/AKT and MEK/ERK pathways on tube formation by HMEC-1 and TIME by using small molecules inhibitors targeting phosphoinositide 3-kinase (PI3K), epidermal growth factor receptor (EGFR), insulin-like growth factor I receptor (IGF-1R), mammalian target of rapamycin (mTOR), mothers against decapentaplegic homolog 3 (SMAD3), and mitogen-activated protein kinase kinase (MEK), (ii) to investigate the effect of blocking PI3K/AKT and MEK/ERK pathways on cell invasion by HMEC-1 and TIME in a 3-D spheroid invasion model by using small molecule inhibitors targeting PI3K, IGF-1R,EGFR, mTOR, Smad3, and MEK. and (iii) to investigate the effect of small molecule inhibitors targeting PI3K, EGFR, IGF-1R, mTOR, Smad3, and MEK on phosphorylation status of AKT and ERK by HMEC-1 and TIME. In vitro angiogenesis was examined using tube formation whereas the invasion properties were assessed using threedimensional (3D) spheroid in vitro invasion assays. PD0325901 and NVP-AEW541 were able to inhibit tube formation by TIME cells in a dose-dependent manner but had no effect on HMEC-1. Western Blot showed MEK inhibitor PD0325901 and IGF-1R inhibitor NVP-AEW541 suppressed phosphorylation of ERK and AKT, respectively, in HMEC-1 and TIME cells. NVP-BKM 120 inhibited tube formation and suppressed phosphorylation of AKT in both cell lines in a dose-dependent manner. TIME spheroids treated with inhibitors (NVP-AEW541, NVP-BKM120 and PD0325901) showed a significant reduction in invasion and a similar trend were observed in suppression of tube formation. However, treatment with PD0325901 showed inhibition in HMEC-1 spheroids invasion whereas there is no suppression in tube formation. HMEC-1 spheroids treated with inhibitors (NVP-BKM120, NVP-BKM120 combination with PD0325901) showed a significant reduction in invasion and a similar trend were observed in suppression of tube formation. This result suggested the different results obtained in response to inhibitors might be due to the different models chosen. In conclusion, our results indicated that tube formation of TIME cell was inhibited when MEK-ERK pathway and/or PI3K-AKT pathway was blocked. In contrast, the angiogenic activity of HMEC-1 cell was inhibited via blockade of PI3K-AKT pathway but not MEK-ERK pathway.